Fortunately, the milk - Gaiman, Neil.; Young, Skottie (New York : Harper, an imprint of HarperCollinsPublishers, 2013)
While picking up milk for his children's cereal, a father is abducted by aliens and finds himself on a wild adventure through time and space.
Keywords: Adventure and adventurers -- Fiction; Space and time -- Fiction; Fathers -- Fiction; Humorous stories